Analisis Naca Airfoil 653-218 Berdasarkan Variasi Mean Aerodynamic Chord Data Pesawat Terbang Dengan Menggunakan Perangkat Lunak Fluent - Bismil Rabeta; Indirwan Haerudin (FTK UNSURYA, 2016)
Aircraft performance can be reviewing by some scientific method. Analytic, numeric and experiment method are three methods that are commonly used. In fact, the research had been done by aircraft manufacturing when they done the design. However, analysis of the resulting data was never published to the mass and communication media as they relate to the interests of the manufacturing company itself. Thus the need for the work done in assessing the performance of aircraft designed and manufactured by several manufacturers. In this study conducted several analyzes of the performance of the NACA airfoil used on the wings of aircraft CN-235 (PT.DI), AIDC-xC2 (AIDC) and 212-Aviocar CASA (EADS-CASA) which has the same NACA airfoil that is 653- 218 but has the geometry and extent of the wing (mean aerodynamic chord / MAC) which is different to using simulation modeling software fluent. Modeling geometry Configuration varied into three configurations with variations in the angle of attack of -4º to 18º. The study concluded that the simulation with the same NACA airfoil with a variation in the length of the MAC will generate value CLmax differently to variations in angle of attack, the value of CL & CD differently to variations in angle of attack, and the value of the lift and drag differ also on the angle of attack.